MOLECULAR DOCKING STUDIES OF FLAVONOIDS FROM SECANG WOOD (Caesalpinia sappan L.) AGAINST GLUCOKINASE ENZYME AS ANTIDIABETIC CANDIDATES - Aurellia, Rizky Natasya; Fitriana, Adita Silvia; Febrina, Dina (Jurnal Farmasi Sains dan Praktis, 2024)
Diabetes mellitus (DM) is a metabolic disease caused by a deficiency of insulin secretion, insulin resistance, and increased hepatic glucose production. Secang wood (Caesalpinia sappan L.) is known to have antihyperglycemic activity. However, these compounds are not yet known. In silico studies are needed to determine the compounds that act as antidiabetics. This study performed molecular docking of flavonoid compounds in sappan wood against the 1V4S glucokinase receptor. The results showed that all flavonoid compounds of sappan wood were predicted to have antidiabetic activity because they had a lower docking score than metformin, the first-line therapy of type 2 diabetes mellitus. Butein is expected to have the best activity. It has the lowest docking score (-94.4836). Visualization of the docking results shows that butein interacts with the identical amino acid residues as metformin, namely ARG 63 and THR 65, through the formation of hydrogen bonds and Van der Waals interactions. SWISS-ADME web tool predicted that butein has good oral absorption and excretion. The toxicity prediction tool showed a slight contradiction in the mutagenic effect. Based on this research, molecular docking may be able to design new drugs, especially from butein in sappan wood (Caesalpinia sappan L.), as antidiabetic candidates.